Diyah (Blood Money) as Substitution to Capital Punishment: An Attempt Towards Harmonisation Between Shari‘ah and Malaysian Penal Code - Awang, A.R.B. (INSI Publications, 2012)
The Islamic Criminal Law (ICL) and The Malaysian Penal Code (MPC) provide capital punishment for cases of intentional murder. Both legal systems also recognised pardon in certain cases. While MPC provides only pardon by Pardon Board, ICL on the other hand, offers three options to the victim’s family, namely, to demand for Qisas(killing in retaliation by the authority), Diyah (Blood Money), and Pardon, the last being the best option and praised by God. In the absence of Diyah under MPC (Act 574) section 302, itis therefore suggested that the provision of Diyah should be included. This is in order to resolve the problems of backlog of murder cases waiting for execution, which is rampant in Malaysia, to response to the call for abolishment of capital punishment and harmonisation process between the said two legal systems.This article will try to look for means and ways for harmonisation between the ICL and MPC. By using Diyah many lives could be saved from the gallows. Diyah is very much encouraged by the Law Giver of Islamic Law. In the past, there was a system of al-‘Aqilah (tribal fund) to pay for blood money. But the system is no longer popular now because of migration and losing structure of family bond. Perhaps, the current system of Takaful (Islamic insurance) can replace and taking its role in Diyah paying process. All these issues will be discussed in details in this article.